Suppressor mutations in ribosomal proteins and FliY restore Bacillus subtilis swarming motility in the absence of EF-P. - Katherine R Hummels; Daniel B Kearns (PLoS Genetics, 2019)
Translation elongation factor P (EF-P) alleviates ribosome pausing at a subset of motifs encoding consecutive proline residues, and is required for growth in many organisms. Here we show that Bacillus subtilis EF-P also alleviates ribosome pausing at sequences encoding tandem prolines and ribosomes paused within several essential genes without a corresponding growth defect in an efp mutant. The B. subtilis efp mutant is instead impaired for flagellar biosynthesis which results in the abrogation of a form of motility called swarming. We isolate swarming suppressors of efp and identify mutations in 8 genes that suppressed the efp mutant swarming defect, many of which encode conserved ribosomal proteins or ribosome-associated factors. One mutation abolished a translational pause site within the flagellar C-ring component FliY to increase flagellar number and restore swarming motility in the absence of EF-P. Our data support a model wherein EF-P-alleviation of ribosome pausing may be particularly important for macromolecular assemblies like the flagellum that require precise protein stoichiometries.